2003
DOI: 10.1097/01.brs.0000067269.31377.6a
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure and Complications of Intradiscal Electrothermal Therapy: A Pilot Study

Abstract: The only risk factor found to be associated with IDET outcome was obesity, which was a strong predictor of failure. Obesity should be considered a relative contraindication to performing IDET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 12 publications
1
70
0
2
Order By: Relevance
“…Unknown (no studies were found on this issue) Safety Some complications have been reported: burning sensations in the legs, which resolved after several weeks; herniation of a disc treated with the procedure and development of radicular pain, numbness and paresis, which resolved after several weeks (Cohen et al 2003); and discitis (Davis et al 2004).…”
Section: Cost/effectivenessmentioning
confidence: 99%
“…Unknown (no studies were found on this issue) Safety Some complications have been reported: burning sensations in the legs, which resolved after several weeks; herniation of a disc treated with the procedure and development of radicular pain, numbness and paresis, which resolved after several weeks (Cohen et al 2003); and discitis (Davis et al 2004).…”
Section: Cost/effectivenessmentioning
confidence: 99%
“…Several low-quality retrospective studies were reported in the literature; results were positive [12] and negative [13][14][15]. Webster et al [16] investigated the outcome of workers' compensation claimants after IDET.…”
Section: Idetmentioning
confidence: 97%
“…According to the literature, complications that occur after IDET include dural puncture, headaches [14], catheter breakage [22,23], nerve root injury, disc herniation [23,24], cauda equina syndrome [25][26][27], vertebral body osteonecrosis [28,29], and discitis [15].…”
Section: Safety Issuesmentioning
confidence: 99%
“…Cohen et al [7] in a research including 79 patients assessed IDET complications and success. While 41 of the 79 patients obtained negative results, the IDET technique was positive for 38 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Three research articles including case series are Freedman et al [5] with 31 patients, Endres et al [6] with 54 patients and Cohen et al [7] with a total of 79 patients. Freedman et al [5] in a study of soldiers with chronic discogenic low back pain included 31 cases with 2 year follow-up from a total of 41 patients who underwent IDET.…”
Section: Discussionmentioning
confidence: 99%